Association between adverse perinatal outcomes and amino acid levels measured with nutrient questionnaire in adolescent pregnancies. Issue 6 (June 2016) - Guzel, Ali Irfan; Cinar, Mehmet; Erkilinc, Selcuk; Aksoy, Rıfat Taner; Yumusak, Omer Hamid; Celik, Fatma; Celik, Yusuf
Abstract : Background : To evaluate the maternal serum amino acid levels in first trimester adolescent pregnancies by using a new developed dietary questionnaire. Methods : A group of 169 pregnant women in the first trimester of their pregnancy were asked to complete the dietary questionnaire. Among all the women, 39 were adolescent pregnancies. The results of the questionnaire were evaluated by a nutrient database program (BeBiS software program) designed to evaluate Turkish traditional foods and commercial processed foods. Results : There was no statistically significant difference between the groups in terms of body mass index and educational and socio‐economic status. The mean age and gravidity was statistically significantly lower in adolescent pregnancies. The mean isoleucine, leucine, lysine, methionine, phenylalanine, tyrosine, threonine, valine, arginine, and proline levels were statistically significantly lower in adolescent pregnancies. Receiver operating characteristic (ROC) curve analysis showed the cut‐off values of these amino acids. Of these amino acids; lower values of histidine, serine, and alanine were associated with lower birth weight, and lower values of histidine and alanine were associated with preterm delivery. Conclusion : To the best of our knowledge, this is the first study evaluating the amino acid levels in adolescent pregnancies. According to this study, some amino acid levels were lower in adolescent pregnancies and associated with adverse perinatal outcomes. Further studies with maternal and perinatal outcomes are needed to demonstrate the effects of these amino acids in such pregnancies.